Novel therapeutic targets for amyotrophic lateral sclerosis - Batra, Gitika (Indian J Pharmacol, 2019)
Amyotrophic lateral sclerosis (ALS) is an untreatable and fatal neurodegenerative disease that is identified by the loss of motor neurons in the spinal cord, brain stem, and motor cortex which theatrically reduces life expectancy. Although the primary cause of ALS remains unclear, its heterogeneity put forward for consideration of association with various factors, including endogenous and/or environmental ones, which may be involved in progressive motor neuron stress that causes activation of different cell death pathways. It is hypothesized that this disease is triggered by factors related to genetic, environmental, and age-dependent risk. In spite of large neurobiological, molecular and genetic research, at the beginning of the 21(st) century, ALS still remains one of the most devastating neurodegenerative diseases because of the lack of effective therapeutic targets. It is a challenge for the clinical and scientific community. A better understanding of the etiology of ALS is necessary to develop specific targets of this progressive neurodegenerative disease. This review states about the current knowledge of targets in ALS research. This review provides an overview of the contribution of different targets like mitochondrial dysfunction, glutamate transport and excitotoxicity, protein accumulation, Oxidative stress, neuromuscular junction, microglia, and other molecular targets in the pathogenesis of ALS.